2009
DOI: 10.1523/jneurosci.0315-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Contribution by the Basolateral Amygdala to Different Forms of Decision Making

Abstract: Impairments in decision making about risks and rewards have been observed in patients with amygdala damage. Similarly, lesions of the basolateral amygdala (BLA) in rodents disrupts cost/benefit decision making, reducing preference for larger rewards obtainable after a delay or considerable physical effort. We assessed the effects of inactivation of the BLA on risk-and effort-based decision making, using discounting tasks conducted in an operant chamber. Separate groups of rats were trained on either a risk-or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
161
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 46 publications
(73 reference statements)
17
161
0
Order By: Relevance
“…Thus, it may be argued that this study's results and, notably, how they differ from previous studies, are due to unintended consequences of experimental design. However, the current methods closely adhered to a physical effort task with BLA inactivations (Ghods-Sharifi et al, 2009). Previous literature noted that loss of BLA function increased latency to choose (Ghods-Sharifi et al, 2009), whereas loss of ACC function increased motor impulsivity as measured by premature responding (Muir et al, 1996); critically, both effects were observed in this study.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Thus, it may be argued that this study's results and, notably, how they differ from previous studies, are due to unintended consequences of experimental design. However, the current methods closely adhered to a physical effort task with BLA inactivations (Ghods-Sharifi et al, 2009). Previous literature noted that loss of BLA function increased latency to choose (Ghods-Sharifi et al, 2009), whereas loss of ACC function increased motor impulsivity as measured by premature responding (Muir et al, 1996); critically, both effects were observed in this study.…”
Section: Discussionsupporting
confidence: 54%
“…As regards effort-based decision making, BLA inactivation decreases preference for high-effort options on both T-maze and operant lever-pressing (ie, physical) paradigms (Floresco and Ghods-Sharifi, 2007;Ghods-Sharifi et al, 2009). This leads to the prima facie assumption that BLA activity overpowers internal representations of cost in order to bias behavior toward highly rewarding options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be the first evidence of true risk-seeking behavior following amygdala damage that is independent of learning. These results are also unlikely to reflect an inability to adapt to changing task contingencies, such as those present in probability-discounting tasks (Ghods-Sharifi et al, 2009). It could be argued that this lesion-induced decline in rGT performance reflects a memory deficit, in that lesioned animals were unable to recall the correct strategy following surgery.…”
Section: Discussionmentioning
confidence: 88%
“…First, the ICSS-mediated discounting task was acquired by rats in the first test session, and stable baseline discounting was achieved in 3 days of testing. This contrasts food reinforcement discounting where typically 10 test sessions are needed for acquisition and 25-35 days are required to reach stable discounting behavior (St Onge et al, 2010;Ghods-Sharifi et al, 2009). Second, ICSS allows for testing several probabilities in a randomized order, a feature that is not successfully implemented with food-reinforced discounting (St Onge et al, 2010).…”
Section: Discussionmentioning
confidence: 99%